Dissociable effects of salience on attention and goal-directed action - Moher, Jeff (Curr Biol, 2015)
Everyday behavior frequently involves encounters with multiple objects that compete for selection. For example, driving a car requires constant shifts of attention between oncoming traffic, rearview mirrors, and traffic signs and signals, among other objects. Behavioral goals often drive this selection process [1–2]; however, they are not the sole determinant of selection. Physically salient objects, such as flashing, brightly colored hazard signs, or objects that are salient by virtue of learned associations with reward, such as pictures of food on a billboard, often capture attention regardless of the individual’s goals [3–6]. It is typically thought that strongly salient distractor objects capture more attention and are more disruptive than weakly salient distractors [7–8]. Counter-intuitively, though, we found that this is true for perception but not for goal-directed action. In a visually-guided reaching task [9–11], we required participants to reach to a shape-defined target while trying to ignore salient distractors. We observed that strongly salient distractors produced less disruption in goal-directed action than weakly salient distractors. Thus, a strongly salient distractor triggers suppression during goal-directed action, resulting in enhanced efficiency and accuracy of target selection relative to when weakly salient distractors are present. In contrast, in a task requiring no goal-directed action, we found greater attentional interference from strongly salient distractors. Thus, while highly salient stimuli interfere strongly with perceptual processing, increased physical salience or associated value attenuates action-related interference.